2020
DOI: 10.3390/jcm9020304
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Markers of Neutrophil Extracellular Trap Formation are Associated with Ischemic Outcomes and Platelet Activation after Peripheral Angioplasty and Stenting

Abstract: Neutrophil extracellular traps (NETs) are supposed to play a central role in atherothrombosis. We measured circulating citrullinated histone H3 (H3Cit) and cell-free DNA (cfDNA), which serve as surrogate markers of NET formation, in 79 patients with peripheral artery disease (PAD) following infrainguinal angioplasty with stent implantation. Analysis of cfDNA and H3Cit was performed using Quant-iT™ PicoGreen® dsDNA Assay Kit or an ELISA, respectively. Within two years of follow-up, the primary endpoint defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Furthermore, they release neutrophil-extracellular traps (NETs), which are able to fight bacteria, but may also exert prothrombotic and proinflammatory effects [ 11 , 28 , 29 ]. In line with these findings, we and others have previously shown associations between markers of NET formation and adverse ischemic events in cardiovascular disease [ 13 , 14 ]. Finally, neutrophils directly interact with platelets via the P-selectin–P-selectin glycoprotein ligand (PSGL)−1 axis as well as via the adhesion molecules glycoprotein (GP) Ib and macrophage−1 antigen [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, they release neutrophil-extracellular traps (NETs), which are able to fight bacteria, but may also exert prothrombotic and proinflammatory effects [ 11 , 28 , 29 ]. In line with these findings, we and others have previously shown associations between markers of NET formation and adverse ischemic events in cardiovascular disease [ 13 , 14 ]. Finally, neutrophils directly interact with platelets via the P-selectin–P-selectin glycoprotein ligand (PSGL)−1 axis as well as via the adhesion molecules glycoprotein (GP) Ib and macrophage−1 antigen [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…As previously shown, activated neutrophils can induce platelet activation [ 11 , 12 ]. Furthermore, neutrophil and platelet activation as well as neutrophil-platelet aggregate (NPA) formation were linked to ischemic outcomes in cardiovascular disease [ 3 , 13 , 14 , 15 ]. Since critical limb ischemia is a frequent consequence of TVR, we sought to investigate whether PLR, NLR or LMR are linked to TVR following elective infrainguinal angioplasty and stenting.…”
Section: Introductionmentioning
confidence: 99%
“…Leukocytes are known to release nuclear contents that form these extracellular traps, which are mainly composed of the histone-DNA complex [ 42 ]. These biomarker levels that lead to extracellular trap formation have been shown to be higher in serum circulation in patients who receive peripheral angioplasty with stent implementation that then develop strokes [ 43 ] and higher in stroke patients with internal artery occlusions [ 44 ]. Our data are the first to report these biomarkers are also associated with iTTP-induced stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, NET formation in the bloodstream can trap other blood cells, resulting in pathological thrombus formation including venous thrombosis ( 8 , 9 ). Several studies have found NETs in ischemic stroke thrombi ( 10 , 11 ) and surrogate markers of NETs in plasma from ischemic stroke patients ( 12 14 ). Similarly, NETs have been reported in brain tissue and plasma of mice subjected to ischemic stroke ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%